Rural farmers’ adaptive and transformative capacity in response to climate change and artisanal small-scale mining in rural Gwanda, Zimbabwe, 1980 to 2021 - Moyo, Vuyisile Precious (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.